Efektivitas Kerja Aparatur Pemerintah Kecamatan dalam Pelayanan Publik - Ulfah Attamimi (LP3M Universitas Muhammadiyah Kendari, 2022)
The effectiveness of sub-district government employees' work in providing public services at the Wua-Wua sub-district office of Kendari city is described in this study.Data will be collected using descriptive qualitative research methodology, including observations, interviews, and literature reviews. There were 11 research informants, consisting of the Camat, Secretary of the Camat, Head of the Integrated Services Section, service staff, and 7 members of the community. Observations or observations of the working atmosphere of employees in public services so that the effectiveness of their performance is illustrated. An interactive model with four stages—data collecting, data reduction, data presentation, and conclusion—was used to examine the obtained data. The study's findings show that employees' efforts are generally effective and helpful to the provision of public services. This is based on factors including productivity, punctuality, and infrastructure accessibility. However, it was discovered from these three factors that the productivity component was not spread equally among all employees. The employees' incompetence, lack of talent, and outside influences are to blame for this predicament.